Two-phase treatment of an Angle Class II division 2 malocclusion - Rapaport Morris (Sciendo, 1998)
This case report describes a two-phase approach to the treatment of an Angle Class II division 2 malocclusion in a growing boy. The first phase utilised a functional appliance (Clark Twin Blocks) du ring puberty and achieved a pleasing improvement in the facial profile. The second phase involved a fixed upper and lower Begg appliance without extractions, followed by retention. An unexpected complication was the failure of the lower left second molar to erupt; surgical removal of cystic elements surrounding this tooth, followed by traction and, later, mechanics to correct the buccal cross-bite, eventually corrected its position.